Influence of Ability, Creativity, and Independent Attitude on Recycling Skills of Junior High School Students - Andi Zulfaida; Elpisah Elpisah; Muhammad Fahreza W; Erni Rismawanti (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study aims to analyze the effect of ability, creativity, and independent attitude of students on the skills of working on waste recycling projects in seventh grade students of SMP Negeri 6 Bulukumba. The study used a quantitative approach with a total sampling method of 49 students. Data were collected through questionnaires and analyzed using multiple regression, t-test, and F-test with the help of SPSS 26. The results showed that the ability, creativity, and independent attitude of students had a positive and significant effect partially or simultaneously on the skills of working on waste recycling projects. The main finding of this study is that students' ability is the most dominant variable in influencing the skills of working on waste recycling projects.